Optimization of enzymatic pretreatment process for enhanced biogas production from palm oil mill effluent - Islam, M.S. Tajul; Alam, Md. Zahangir; Mamun, Abdullah Al (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Through anaerobic digestion (AD) of organic waste, biogas is being currently produced. By the aid of different type of microbes through four sequential processes, AD is executed by the hydrolysis, acidogenesis, acetogenesis and methanogenesis. To achieve efficient production of biogas, nutrients and suitable process conditions for micobes are two main prerequisite. Microbes cannot consume complex substances as their food and energy at the beginning of the growth. During hydrolysis, complex compounds (polymers) are converted into simple monomers so that microbes can take the monomers as their food and energy easily. Hydrolysis is the slow process of AD. Enzyme application is one of the efficient and environmentally friendly techniques as enzyme increases the rate of conversion in hydrolysis with minimum pollution. In this study, three parameters influencing biogas production were optimized by response surface methodology (RSM) based on face-centered central composite design (FCCCD). In statistical optimization maximum 835 ml biogas with 85% COD removal was observed from 50 ml of POME after 10 days of operation.